Analisis Pemecahan Masalah Matematika pada Materi Perbandingan untuk Siswa Kelas VII SMP Negeri I Kota Tambolaka - Bulu, Agustina Rovina; Lede, Yulius Keremata; Ate, Dekriati (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this research is to find out how students solve problems on comparative material questions at SMP Negeri 1 Tambolaka City. This type of research is qualitative research. The subjects of this research were all class VIIE students at SMP Negeri 1 Tambolaka City, totaling 29 students. The data collection techniques used were written tests, interviews, and documentation. Based on the research results above, it can be concluded that the analysis of mathematical problem solving in comparative material for class VIIE students at SMP Negeri I Tambolaka City from the results of the research is that there are still students who are not able to identify known/asked elements, formulate mathematical problems or construct models. mathematics, applying strategies to solve problems and explaining or interpreting results according to the initial problem. Of the 29 students, the researcher chose 6 students to be interviewed according to the NCTM indicators